Internet of Things as Engine of Economic Growth in Indonesia - Bambang Widagdo; Mochamad Rofik (Indonesian Journal Of Business And Economics, 2019)
The economic diversification concept gives hope for a country with rich natural resources to strengthen its economic basis. Thus industrial revolution era of 4.0 provides great opportunity to fasten the process. A study by McKensey in 2011 proved that the internet in the developing country contributes around 3.4% towards its GDP which means that the internet has become a new hope for the economy in the future. Indonesia is one of the countries that is attempting to maximize the role of the Internet of Things (IoT) for its economic growth.  The attempt has made the retail and tourism industries as the two main sectors to experience the significant effect of IoT. In the process of optimizing the IoT to support the economic growth, Indonesia faces several issues especially in the term of the internet network quality and its distribution, the inclusive access of financial access and the infrastructure